2020
DOI: 10.1021/acsphotonics.0c00614
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Spin Defects in Hexagonal Boron Nitride

Abstract: Two-dimensional hexagonal boron nitride offers intriguing opportunities for advanced studies of light–matter interaction at the nanoscale, specifically for realizations in quantum nanophotonics. Here, we demonstrate the generation of optically addressable spin defects based on the negatively charged boron vacancy (VB –) center. We show that these centers can be created in exfoliated hexagonal boron nitride using a variety of focused ion beams (nitrogen, xenon, and argon). Using a combination of laser and reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
131
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(151 citation statements)
references
References 39 publications
18
131
2
Order By: Relevance
“…Spin carrying defects have been theoretically predicted and experimentally confirmed in hBN 15 – 19 . Currently, the most understood defect is the negatively-charged boron vacancy center ( ) 20 , which can be readily created by neutron irradiation, ion implantation, or femtosecond laser pulses 21 , 22 . Due to its spin-optical properties, the center is proving to be a promising candidate system for quantum information and nanoscale quantum sensing applications and has thus expanded the already large suite of unique features displayed by 2D materials 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Spin carrying defects have been theoretically predicted and experimentally confirmed in hBN 15 – 19 . Currently, the most understood defect is the negatively-charged boron vacancy center ( ) 20 , which can be readily created by neutron irradiation, ion implantation, or femtosecond laser pulses 21 , 22 . Due to its spin-optical properties, the center is proving to be a promising candidate system for quantum information and nanoscale quantum sensing applications and has thus expanded the already large suite of unique features displayed by 2D materials 13 .…”
Section: Introductionmentioning
confidence: 99%
“…A near-infrared wide PL band around λ = 810 nm is observed in the sample after the irradiation procedure previously shown to arise due to the presence of defects [ 21 ]. We also note that the 532 nm (2.33 eV) excitation used for the excitation of the PL spectrum is within the optical absorption band of defects, as was previously revealed by low-temperature photoluminescence excitation spectroscopy [ 30 ]. There, it was also shown that the PL spectrum of defects at a low temperature does not possess any narrow peaks within the emission wavelength.…”
Section: Resultsmentioning
confidence: 56%
“…After electron irradiation, a weak wide PL band in the visible (VIS) spectral range appears. However, in previously published papers devoted to the PL properties of the defect, this broad band was not observed [ 21 , 30 ]. In Ref.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, ion implantation can also be used to introduce the boron-vacancy, like ion beams (E.g. nitrogen, xenon, and argon) (Kianinia et al, 2020).…”
Section: Nitrides With Defectsmentioning
confidence: 99%